Stenotrophomonas maltophilia resistant to trimethoprim - sulfamethoxazole: an increasing problem - Al-Jasser Asma (BMC, 2006)
Abstract Stenotrophomonas maltophilia (S. maltophilia) has recently emerged as an important nosocomial pathogen. Treatment of invasive infections caused by this organism is difficult as the bacterium is frequently resistant to a wide range of commonly used antimicrobials. Trimethoprim-sulfamethoxazole (TMP - SXT) is recommended as the agent of choice for the treatment of S. maltophilia infections. However, the development of resistance to this antibiotic represents a real challenge to laboratorians and clinicians. This letter describes the first isolation of S. maltophilia resistant to TMP - SXT from two patients treated at Riyadh Armed Forces Hospital which is a major tertiary hospital in Saudi Arabia.